Age dependency of ischaemic stroke subtypes and vascular risk factors in western Norway: the Bergen Norwegian Stroke Cooperation Study - Nacu, A. (Acta Neurol Scand, 2015)
OBJECTIVES: Age dependency of acute ischaemic stroke aetiology and vascular risk factors have not been adequately evaluated in stroke patients in Norway. Aims of this study were to evaluate how stroke subtypes and vascular risk factors vary with age in a western Norway stroke population. MATERIALS AND METHODS: Patients aged 15–100 years consecutively admitted to our neurovascular centre with acute ischaemic stroke between 2006 and 2012 were included. The study population was categorized as young (15–49 years), middle‐aged (50–74 years) or elderly (≥75 years). Stroke aetiology was defined by TOAST criteria. Risk factors and history of cardiovascular disease were recorded. RESULTS: In total, 2484 patients with acute cerebral infarction were included: 1418 were males (57.3%). Mean age was 70.8 years (SD ± 14.9), 228 patients were young, 1126 middle‐aged, and 1130 were elderly. The proportion of large‐artery atherosclerosis and of small‐vessel occlusion was highest among middle‐aged patients. The proportion of cardioembolism was high at all ages, especially among the elderly. The proportion of stroke of other determined cause was highest among young patients. Some risk factors (diabetes mellitus, active smoking, angina pectoris, prior stroke and peripheral artery disease) decreased among the elderly. The proportions of several potential causes increased with age. CONCLUSION: The proportion of stroke subtypes and vascular risk factors are age dependent. Age 50–74 years constitutes the period in life where cardiovascular risk factors become manifest and stroke subtypes change.